Guiding, sustaining and growing the public involvement of young people in an adolescent health research community of practice. (27th October 2022) - Swist, Teresa; Collin, Philippa; Nguyen, Betty; Davies, Cristyn; Cullen, Patricia; Medlow, Sharon; Skinner, S. Rachel; Third, Amanda; Steinbeck, Katharine
Abstract: Background: Public involvement in health research and its translation is well recognized to improve health interventions. However, this approach is insufficiently practised and evidenced in relation to young people. This paper presents an analysis of the process of co‐producing a framework, partnership model and a growing network of young people informing and guiding an adolescent health research community of practice. Methods: A Living Lab is a participatory research approach that brings together a broad range of stakeholders in iterative cycles of research, design, development, pilot‐testing, evaluation and delivery to implement effective responses to complex phenomena. The geographical setting for this study was Sydney, NSW, Australia, and involved both youth and adult stakeholders from this region. The study spanned three phases between July 2018 and January 2021, and data collection included a range of workshops, a roundtable discussion and an online survey. Results: The co‐production process resulted in three key outputs: first, an engagement framework to guide youth participation in health research; second, a partnership model to sustain youth and adult stakeholder collaboration; third, the growth of the public involvement of young people with a range of projects and partners. Conclusions: This study investigated the process of co‐producing knowledge with young people in an adolescent health community of practice. A reflexive process supported youth and adult stakeholders to collaboratively investigate, design and pilot‐test approaches that embed young people's engagement in adolescent health research. Shared values and iterative methods for co‐production can assist in advancing mutual learning, commitment and trust in specific adolescent health research contexts. Public Contribution: Young people guiding and informing an adolescent health research community of practice were involved in this study, and one of the participants is a paper co‐author.